1999
DOI: 10.1038/sj.ejcn.1600868
|View full text |Cite
|
Sign up to set email alerts
|

Early nutrition, essential fatty acid status and visual acuity of term infants at 7 months of age

Abstract: Objective: In term infants the relationship between visual acuity and dietary fatty acid composition is not consistent, possibly due to confounders, which were mostly neglected in the studies concerned. In the current study, therefore, the in¯uence of the essential fatty acid status and potential confounders on the visual acuity was investigated. Design: The essential fatty acid status was determined at 7 months of age in red blood cell and plasma phospholipids of breastfed and formula-fed infants, born at ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The scores were highest in infants whose mothers consumed more than 2 fish meals per week but had hair mercury levels below 1.2 µg/g hair (Oken et al, 2005). Bakker et al (1999; could not demonstrate an association between feeding modus (breast-milk or infant formula) or DHA concentrations in umbilical venous plasma and plasma phospholipids at age 7 years on the one side and visual acuity at 7 months of age nor with intelligence at age 7 years on the other side.…”
Section: Visual Function and Cognitive Developmentmentioning
confidence: 82%
“…The scores were highest in infants whose mothers consumed more than 2 fish meals per week but had hair mercury levels below 1.2 µg/g hair (Oken et al, 2005). Bakker et al (1999; could not demonstrate an association between feeding modus (breast-milk or infant formula) or DHA concentrations in umbilical venous plasma and plasma phospholipids at age 7 years on the one side and visual acuity at 7 months of age nor with intelligence at age 7 years on the other side.…”
Section: Visual Function and Cognitive Developmentmentioning
confidence: 82%
“…However, it has been hypothesized that prenatal exposure to DHA may also affect later development through fetal programming of the central nervous system and various other physiologic pathways. This possibility is supported by a number of observational studies that associate DHA status during pregnancy with positive long-term effects on the offspring (713). Several randomized trials of maternal DHA supplementation during pregnancy and/or lactation have been conducted with mixed results; the larger trials have not reported advantages for DHA supplementation during the first 18 months (1416), although one small study found positive effects on problem solving (17).…”
Section: Introductionmentioning
confidence: 86%
“…Studies of infant visual function have been widely conducted in this area for some time (e.g., Ref. 17), showing both positive (18)(19)(20)(21)(22)(23)(24)(25)(26) and null (27)(28)(29)(30)(31) effects for LC-PUFA supplementation. The choice of dependent variable within this realm is perhaps facilitated by the fact that there is a finite set of such measures for visual function (e.g., acuity or contrast sensitivity), and that the standardized measures that do exist (e.g., Ref.…”
Section: Infant Cognition and Long-chain Polyunsaturated Fatty Acids mentioning
confidence: 99%